2005
DOI: 10.1111/j.1478-3231.2005.01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine and soluble cytokine receptor levels in patients with non‐alcoholic steatohepatitis

Abstract: This study shows that circulating TNF-alpha/sTNFR1 and IL-6/sIL-6R levels are significantly increased in NASH patients as compared with simple steatosis patients and healthy volunteers, and that these increased levels may be implicated in the pathogenesis of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
134
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 32 publications
6
134
1
5
Order By: Relevance
“…NAFLD can promote atherogenic dyslipidemia and contribute to CKD pathogenesis -as well as to accelerated atherogenesis -through the release of some pathogenetic mediators from the steatotic liver, including increased C-reactive protein and other inflammatory cytokines (26). Importantly, several studies have shown that these potential mediators of vascular and kidney damage are markedly higher in patients with NAFLD than in those without (26)(27)(28)(29)(30)(31), and are thought to be pathogenic factors for the development of CKD (32)(33)(34)(35). Consistent with the hypothesis that liver inflammation (or other liverderived factors) in NAFLD may play a role in kidney disease progression, it has been shown that type 2 diabetic subjects with chronic hepatitis B virus infection were more likely to develop end-stage renal disease compared with those not infected with hepatitis B virus (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAFLD can promote atherogenic dyslipidemia and contribute to CKD pathogenesis -as well as to accelerated atherogenesis -through the release of some pathogenetic mediators from the steatotic liver, including increased C-reactive protein and other inflammatory cytokines (26). Importantly, several studies have shown that these potential mediators of vascular and kidney damage are markedly higher in patients with NAFLD than in those without (26)(27)(28)(29)(30)(31), and are thought to be pathogenic factors for the development of CKD (32)(33)(34)(35). Consistent with the hypothesis that liver inflammation (or other liverderived factors) in NAFLD may play a role in kidney disease progression, it has been shown that type 2 diabetic subjects with chronic hepatitis B virus infection were more likely to develop end-stage renal disease compared with those not infected with hepatitis B virus (36).…”
Section: Discussionmentioning
confidence: 99%
“…In these analyses, we combined subjects with eGFR [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The association between serum bilirubin and eGFR (included as continuous variable) was investigated using linear (unadjusted and fully adjusted) regression models in the whole group and in subgroups of participants stratified by diabetes status (Table 3). We excluded subjects who had a serum creatinine concentration )176.8 mmol/L ()2.0 mg/dL) or serum bilirubin concentrations )22.23 mmol/L ()1.3 mg/dL) (ns513).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species: cytochrome P-450, 111 myeloperoxidase, nitric oxide synthase, lipid peroxidation products such as oxidized LDL, thiobarbituric acid-reacting substances 112 2. Inflammatory: TNFa, 113 adiponectine, 57,58,114,115 CRP, 48,83 visfatin, resistin, interleukin-6 and retinol binding protein-4 75,82 3. Apopetosis: cytokine-18 51,52 and fibrosis: hyaluronic acid 114 Table 2 represents the research results about the role of this group in predicting NASH.…”
Section: Biomarkersmentioning
confidence: 99%
“…111 Increased expression of proinflammatory cytokines such as TNFa and interleukin1b was may be responsible for observed decreases in respective P-450 activity. [113][114][115][116][117] Original European Liver Fibrosis study used age, tissue inhibitor of matrix metalloproteinase 1, hyaluronic acid, amino-terminal peptide of procollagen III for detection of fibrosis in fatty liver. In contrast, pathologists' agreement over histological scores ranged from very good to moderate (k ¼ 0.97-0.46).…”
Section: Biomarkersmentioning
confidence: 99%
“…Some of these FFAs are stored as triglycerides that higher levels of proinflammatory cytokines [tumor necrosis factor-α and interleukin (IL)-6] when compared to SS patients. Unfortunately, we cannot use these cytokines as noninvasive markers for predicting the presence of NASH because the differences have not been significant enough [38,39] . Many potential biomarkers have been studied with conflicting results.…”
Section: Nash Pathophysiologymentioning
confidence: 99%